TRANSFORMASI PENDIDIKAN ORANG RIMBA: Menyelaraskan Pola Pengajaran dengan Pedoman Agama Islam untuk Pembentukan Karakter - Asniah, Asniah; Badrudin, Badrudin; Ulfiah, Ulfiah (ILJ: Islamic Learning Journal, 2024)
This research explores the implementation of teaching patterns with Islamic religious guidelines for Orang Rimba in Dwi Karya Bhakti Hamlet, with a focus on character education, basic education, counseling for parents and children, and providing assistance for educational facilities and infrastructure. This research involves the stages of identifying needs and implementing educational programs, with the aim of increasing the participation and quality of education of Orang Rimba children. The results provide a comprehensive picture of the efforts made to improve their education system, overcome obstacles such as the lack of facilities, and increase community awareness of the importance of formal education. The conclusion of this study shows that although there are still obstacles, these efforts provide a positive foundation for the development of faith-based character and access to education for Orang Rimba children in Dwi Karya Bhakti Hamlet. Facilities and infrastructure assistance is expected to be an important impetus for further changes in their education system.